Correlation between obstructive sleep apnea and hypoperfusion in patients with acute cerebral infarction - Zhou, Yi; Jin, Xiaomei; Liu, Xiaorong; Tang, Jiafan; Song, Liyan; Zhu, Yu; Zhai, Wanqing; Wang, Xianhui (Frontiers in Neurology, 2024)
To explore the relationship between obstructive sleep apnea (OSA) and hypoperfusion during ultra-early acute cerebral infarction. Patients and methods: Data were retrospectively collected from patients admitted to our hospital with acute cerebral infarction between January 2020 and January 2022, who underwent comprehensive whole-brain computed tomography perfusion imaging and angiography examinations within 6 h of onset. The F-stroke software automatically assessed and obtained relevant data (Tmax). The patients underwent an initial screening for sleep apnea. Based on their Apnea-Hypopnea Index (AHI), patients were categorized into an AHI ≤15 (n=22) or AHI >15 (n=25) group. The pairwise difference of the time-to-maximum of the residue function (Tmax) > 6 s volume was compared, and the correlation between AHI, mean pulse oxygen saturation (SpO2), oxygen desaturation index (ODI), percentage of time with oxygen saturation < 90% (T90%), and the Tmax > 6 s volume was analyzed. Results: The Tmax > 6 s volume in the AHI > 15 group was significantly larger than that in the vs 59(21-106) mL, p =0.013]. Spearman's correlation analysis revealed Tmax > 6 s volume was significantly correlated with AHI, mean SpO2, ODI and T90% in the AHI > 15 group, however, no significant correlations were observed in the AHI ≤ 15 group. Controlling for the site of occlusion and Multiphase CT angiography (mCTA) score, AHI (β = 0.919, p < 0.001), mean SpO2 (β = -0.460, p = 0.031), ODI (β = 0.467, p = 0.032) and T90% (β =0.478, p = 0.026) remained associated with early hypoperfusion in the AHI > 15 group. Conclusion: In patients with acute cerebral infarction and AHI > 15, AHI, mean SpO2, ODI and T90% were associated with early hypoperfusion. However, no such relationship exists among patients with AHI ≤ 15.